INDICATOR DEVELOPMENT AND QUALITY OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE FOR THE MINING INDUSTRY IN INDONESIA (Qualitative Study During Observation Period 2017-2019) - Temy Setiawan; Nicholas Jonathan; Kurniawati Kurniawati (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2022)
Disclosure of corporate social responsibility (CSR) is increasing in urgency because demands for legitimacy are increasing. Companies can disclose their CSR through annual reports or sustainability reports. This study aims to provide information on how many companies have disclosed CSR in their sustainability reports, the average extent of disclosure in annual reports and sustainability reports, which indicators are predominantly disclosed and which disclosures are limited. This research is a descriptive qualitative study using secondary data taken from the website company's official in the form of an annual report and a sustainability report and then analyzed by reference to the GRI-G4 and/ or GRI-standards using quantitative and qualitative content analysis techniques. The result of the research is that the company disclosure of CSR using sustainability reports is only 20%; and the rest is still in the annual report. General indicators disclosed based on GRI-G4 and GRI-standard are positive and non-monetary disclosures, especially on sensitive indicators because they are private to the company. This study also provides a qualitative measurement (measurement of variety) of CSR disclosure involving tables/ photos/ diagrams in addition to general narrative disclosures in quantitative content analysis techniques as a new measurement nowadays. Keywords: GRI-Standard; GRI-G4; CSR disclosure, a qualitative content analysis technique